Peran Komunikasi Internal terhadap Efektivitas Kerja dan Kinerja Karyawan pada Dinas Ketahanan Pangan Provinsi Jambi - Mega Isabella Sitinjak; Zulfina Adriani; Feny Tialonawarmi (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to explore the role of internal communication on work effectiveness and employee performance at the Jambi Province Food Security Service. Internal communication is a key factor in increasing organizational efficiency and productivity, especially in the government context. The research approach used is qualitative with descriptive methods, aiming to understand the experiences, perceptions and dynamics of interactions between employees and management. Data was obtained through in-depth interviews with 3 participants consisting of structural officials and functional employees, as well as through direct observation of communication patterns in the work environment. The research results show that effective internal communication characterized by openness of information, active participation of all parties, and transparent two-way communication contributes significantly to increasing work effectiveness and employee performance. Employees who feel they have received sufficient information and are involved in decision making are more motivated and show better performance.